Challenges in Implementing Smoking Prevention Efforts in Indonesia: An Analysis from a Hadith Perspective - Harahap, Sahlan (Yayasan Albahriah Jamiah Indonesia, 2025)
In 1987, the World Health Organization (WHO) declared May 31 as World No Tobacco Day to address the tobacco epidemic and smoking-related deaths. In 2017, the WHO stated that the tobacco industry was a major contributor to the global pollution crisis, impacting the health and well-being of people worldwide. In line with WHO goals, the Indonesian Ministry of Health proposed several policies to reduce cigarette and nicotine addiction among the younger generation. However, the Indonesian government has not fully supported the Ministry of Health's proposed policies. This research uses qualitative methods with descriptive-analytical data analysis techniques. It examines hadiths with the theme of preventing harm in the al-Sittah pole to propose guidelines for resolving the dilemma of consistency in the smoking and nicotine prevention agenda in Indonesia. The study found that implementing a comprehensive smoking prevention agenda in Indonesia is necessary to ensure public health and environmental sustainability. In conclusion, policy implementation initiatives, such as revising Government Regulation Number 109/2012 to prevent the smoking culture in Indonesia, must be implemented in line with the demands for protecting mental well-being in maqāṣid al-Syariah (Objectives of Islamic Divine Law).